Photopolymerization of hydrogel using three types of cross-linking agents: effects of water content, mechanical and thermal properties - Dhuha Jawad Hussein; Marwa Satar; Ali Khudhair Al-Hamzawi; Hind Shabbani; Mohammed Ali Mutar; Mohd Roslee Othman (South African Journal of Chemical Engineering, 2025)
In the present work, a series of polymeric hydrogels composed of 2-hydroxyethyl methacrylate (HEMA) and three types of cross-linking agents, namely 1,6-hexanediol diacrylate (HDODA), ethylene glycol dimethacrylate (EGDMA), and triethylene glycol dimethacrylate (TEGDA), were synthesized by free radical photopolymerization. The cross-linking agents were used to obtain hydrophilic polymers. The cross-linked polymers have improved resistance to chemical and thermal degradation. The structures of polymeric hydrogels have been investigated intensively using FTIR to verify the obtained structures. Mechanical properties, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) were performed. The mechanical properties indicate that the introduction of TEGDA into hydrogel has the highest stress and strain, and the cross-linking using TEGDA achieves the best Young's modulus of elasticity at low water content compared to EGDMA and HDODA cross-linking. The results of TGA show that the incorporation of TEGDA and HDODA into the hydrogel structures increases the onset temperatures to 280 °C and 275 °C, respectively, compared to EGDMA, which has an onset temperature of around 190 °C. The equilibrium water content (EWC%) was measured at different experimental conditions, and results showed that HDODA gives the highest water content of 37 %, while TEGDA gave the lowest water content of 31 %.